Early Adolescent Substance Use as a Risk Factor for Developing Conduct Disorder and Depression Symptoms - Wymbs, Brian T. (Rutgers University, 2014)
OBJECTIVE: Conduct disorder and depression symptoms are well-established risk factors for substance use during adolescence. However, few investigations have examined whether early substance use increases adolescents’ risk of developing conduct disorder/depression symptoms. METHOD: Using the Developmental Pathways Project sample of 521 middle school students (51.6% male), we tested whether substance use (indicated by alcohol and marijuana use, and use-related impairment) in 8th and 9th grade increased risk of conduct disorder and depression symptoms in 9th and 12th grade over and above prior symptoms. We examined whether associations between substance use and conduct disorder/depression symptoms were consistent across self- or parent-reported symptoms and whether associations were moderated by gender. RESULTS: Analyses indicated that, over and above prior symptoms, elevated substance use in 8th grade predicted elevated conduct disorder symptoms in 9th grade, and substance use in 9th grade predicted conduct disorder symptoms in 12th grade. In contrast, substance use failed to predict later depression symptoms independent of prior symptoms. These findings were consistent across self- and parent-reported conduct disorder/depression symptoms. With one exception (association between substance use in 8th grade and self-reported conduct disorder symptoms in 9th grade), relations between early substance use and later conduct disorder symptoms did not differ between boys and girls. CONCLUSIONS: Study findings underscore the unique contribution of substance use during early adolescence to the development of conduct disorder symptoms by late adolescence.